LAMA FERMENTASI TERHADAP MUTU TEH DAUN SIRSAK (Annona muricata L.) - Tanjung, Riski '; Hamzah, Faizah '; Efendi, Raswen ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purposes of this study was to obtain the effect of fermentation on the quality of soursop leaf tea by fermentation. Soursop leaf tea processing using the method of processing black tea. The method used in this study was completely randomized design with 4 treatments and 4 replications. The treatment used were F1(1 hour fermentation), F2 (2 hours fermentation), F3 (3 hours fermentation),        F4 (4 hours fermentation). The results showed that the long of fermentation of tea leaves of the soursop significant effect on water content, levels of tannins, antioxidant activity, assessment of sensory descriptive and hedonic well as colour, aroma, taste and acceptance as a whole tea leaves of the soursop, but did not significantly affect the ash content. The best treatment was F4 (4 hours fermentation) based on water content of 1.31%, ash content of 5.82%, tannin content of 0.51%, the antioxidant levels of 28.733 ppm, descriptive sensory assessment and hedonic soursop leaf tea which has a brown colour and preferred by the panelist’s. Soursop leaf tea flavor is slightly tart and flavorful leaves of the soursop so preferred by the panelist’s. While the overall assessment of soursop leaf tea is also preferred by the panelist’s.   Keywords : Tea, quality, soursop leaves, long fermentation.